Effect of titanium addition on microstructure and mechanical properties of WC-Ni3Al cemented carbide - WU Zuji; FAN Jiafeng; LI Jingmao; ZHU Dezhi; QU Shengguan; LI Xiaoqiang (Cailiao gongcheng, 2022)
Ti-doped WC-Ni3Al cemented carbide was prepared by spark plasma sintering for improving mechanical properties. The effect of different Ti contents on the microstructure and mechanical properties of WC-Ni3Al cemented carbide was investigated. The results show that due to Ti addition, the small amount of Al2O3reactively formed in WC-Ni3Al is smaller and more uniform than the sintered sample without adding Ti. The refinement of Al2O3 and the in-situ (Ti, W) C synergistically enhance the hardness of the WC-Ni3Al cemented carbide. Meanwhile, the fracture toughness is improved because the in-situ (Ti, W)C and WC have a better interface combination, facilitating the bridging and deflection formation of cracks. The WC-Ni3Al cemented carbide with 3% (mass fraction) Ti obtains the optimal mechanical properties, with hardness of (19.29±0.18) GPa and fracture toughness of (13.14±0.24) MPa·m1/2.